Deduaian Tradition in Lampung Saibatin Traditional Marriage in Review of Islamic Law - Saraswati, Annisa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to analyze the practice of the deduaan tradition in traditional Lampung Saibatin marriages in Bandar Lampung City and to analyze the Islamic legal review of the practice of the deduaan tradition in traditional Lampung Saibatin marriages in Bandar Lampung City. This study employs a qualitative method with a descriptive-analytical approach through field research, analyzing data directly from the research site. The results of the research show that the practice of deduaan before the marriage in Bandar Lampung City first requires an agreement/permission to be made by the family who has the intention and asks permission from the inner traditional leaders. Second, notification to the entire community, traditional leaders, religious and government leaders door to door. Kegita, the implementation of the deduaan is carried out in the afternoon in Batanghari accompanied by the ladies/bodyguards called the Mena Tribe, Dukhi Tribe, Kanan Tribe and Kikhi Tribe, after completion the bride and groom are made up again and wear traditional clothes, then on the way to the wedding house they are paraded. wine. The deduaian tradition in Islam is grouped into authentic customs or urf, namely customs that are repeatedly carried out and accepted by many people. This research contributes to providing the people of Lampung with information about the deduaian process through stories and traditional ceremonies, ensuring the preservation of their traditions. It also emphasizes the importance of safeguarding cultural heritage and promotes cross-cultural understanding at a global level.